The Role of Workshops Using the DECODE Online Model in Supporting STEM Teachers’ TPACK Competence in Teaching Inquiry Skills - Devi Kurnia Andri Wardatul Jannah; Rifati Dina Handayani; Bevo Wahono (Universitas Pendidikan Ganesha, 2025)
Strengthening teachers’ Technological Pedagogical Content Knowledge (TPACK) has become an urgent need in STEM education, particularly to support the development of students’ investigative skills. This study aims to analyze the effectiveness of an online workshop based on the DECODE model in enhancing STEM teachers’ TPACK, as well as to explore the challenges, constraints, and benefits perceived by participants after completing the workshop. The study employed a descriptive qualitative approach involving 60 STEAM teachers as participants. The workshop was conducted online using the Cloud Classroom (CCR) platform and Zoom Meeting. The DECODE model was implemented through three main stages: DEmonstration, CO-train/design/teach, and DEbrief. Data collection techniques included workshop observations, open-ended questionnaires, and in-depth interviews, using observation guidelines and semi-structured interview protocols as instruments. The data were analyzed using thematic analysis, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the use of CCR in the DECODE workshop supported teachers’ improvement in designing investigative learning, stimulated students’ curiosity, and facilitated technology-based investigative processes. In addition, participants reported positive responses to the collaborative and reflective workshop model. The study concludes that online workshops based on the DECODE model have strategic implications for improving the quality of STEM teaching through strengthening teachers’ TPACK.